Electron Paramagnetic Resonance Study of Thermally Treated Bismuth Subgallate - Paweł Ramos; Barbara Pilawa (Bioinorganic Chemistry and Applications)
Complex of bismuth, an anti-inflammatory drug, was studied by EPR spectroscopy. The aim of this study was to determine concentrations and properties of free radicals formed during thermal sterilization of bismuth subgallate according to pharmacopoeia norms to optimize its sterilization process. Different temperatures (160°C, 170°C, and 180°C) and times (120 minutes, 60 minutes, and 30 minutes) of sterilization were used. Interactions of bismuth subgallate with DPPH, the model free radical reference, were checked. g-Factors, amplitudes (A), integral intensities (I), and linewidths (ΔBpp) were obtained. Integral intensities were obtained by double integration of the first-derivative EPR lines. The influence of microwave power in the range of 2.2–70 mW on shape and parameters of the EPR spectra was examined. Thermal sterilization produced free radicals in bismuth subgallate in all tested cases. Strong interactions with free radicals were pointed out for all the analysed samples containing bismuth independent of sterilization conditions. Optimal conditions of thermal sterilization for bismuth subgallate with the lowest free radical formation are temperature 170°C and time of heating 60 minutes. Strong dipolar interactions exist in thermally sterilized bismuth subgallate. EPR spectroscopy is a useful method of examination of thermal sterilization conditions.